Psychosocial factors and dealing with work stress in university teachers, a systematic review - Carolina Viviana Rivela Viladesau; Alejandro Lanuque; Suzaneide Oliveira Medrado; Julieta Marmo; Selediana De Souza Godinho (Perspectivas Metodológicas​)
This systematic review study analyzed the repercussions of psychosocial factors for coping with work-related stress in university teachers. The PRISMA-NMA statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) was used on the Dialnet, SciELO and Redib databases with a sample size of 5417 teachers. Results: 48% presented elevated dissatisfaction in detrimental working conditions, 36% displayed cognitive dysfunction, 12.3% resigned citing Burnout Syndrome and 3.7% presented self-care, self-control, and positive reassessment and sought out support.